How (the Lack of) Representation in Television Affects College Students' Social-Emotional Well-Being - Bromberg Gaber, Aliza. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Child Development.; Advisor: Julie Dobrow.; Committee: Chip Gidney, and Natalie Engel.; Keyword: Social research.